Analysis of airborne dust effects on terrestrialmicrowave propagation in arid area - Elfatih A. A. Elsheikh; Islam Md. Rafiqul; Mohamad Hadi Habaebi; Ahmad F. Ismail; Z. E. O. Elshaikh; F. M. Suliman; Jalel Chebil (Bulletin of Electrical Engineering and Informatics, 2019)
Sand and dust storms are environmental phenomena ,during these storms optical visibility might be decreased, consequently, atmospheric attenuation is clearly noticed.Micro-wave (MW) and Milimeter-wave (mm) propagation is severely affected by dust and sand storms in considerable areas around the world. Suspended dust particles may directly cause attenuation and cross polarization to the Electromagnetic waves propagating through the storm. In this paper, a thorough investigation of dust storm characteristics based onmeasured optical visibility and relative humidity is presented. In addition,the dust storms effects of on Micro-wave and Millimeter-wave propagation have been studied based on data measured Received Signal levels (RSL)and dust storm characteristics synchronously. Analyticaldustattenuationmodels predictions are matched to the measured attenuationdata at 14 GHz and 21 GHz. It has been found that the measured attenuation is approximately ten times higher than the predicted attenuation for both frequencies.